Peningkatan Kemampuan Mengembangkan Ide Pokok Paragraf Dengan Metode Picture and Picture Pada Siswa Kelas V SDN Mangunjiwan 2 Kecamatan Demak - Amin, Nur; Suci, Wiji Lestari Candra (Jurnal Kualita Pendidikan, 2024)
Writing is a language competency that exists in every level of education, from preschool to college. The purpose of this study was to improve the ability to develop main ideas in paragraphs in grade V students of SDN Mangunjiwan 2, Demak District using the picture and picture method. This type of research is Classroom Action Research (CAR) with four stages, namely planning, action, observation and reflection. This study was conducted in two cycles. The subjects in this study were 18 grade V students of SDN Mangunjiwan 2, Demak District. Data collection techniques in this study were tests, observations, interviews and documentation. The indicators of success in this study are for individual learning provisions if the proportion of students' correct answers is more than the KKM that has been set and for classical learning completeness if at least 70% of all students have achieved KKM. The results of the study from cycle I obtained classical completeness of 67% with 12 students completing, while the results of cycle II classical completeness of 83% with 15 students so that the indicators of success were achieved in cycle II.